Prediction of neutralising antibodies for novel coronavirus with machine learning - Kho, Jordon Junyang (Nanyang Technological University, 2023)
Coronaviruses were responsible for three major viral outbreaks since the beginning of the 21st century, with the most recent outbreak being the coronavirus disease 2019 pandemic caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Coronavirus infections are known to cause severe respiratory disease and even death. Unfortunately, there is no effective drug or treatment to prevent and treat the infection. While neutralising antibodies have the potential to prevent future infections, traditional lab-based methods are often too time-consuming and expensive. Hence, machine learning approaches have become increasingly popular for expediting and complementing lab-based methods in the search for potential antibody candidates.